Primary immune‐mediated haemolytic anaemia: a retrospective long‐term study in 61 dogs. Issue 12 (27th August 2019) - Weingart, C; Thielemann, D; Kohn, B
Abstract : Objectives: The objective of this study is to describe the course of disease of dogs with primary immune‐mediated haemolytic anaemia (pIMHA) with an observation period longer than 90 days in regard to clinical signs, laboratory results and treatment response. Material and methods: Clinical records between January 2003 and December 2011 were reviewed. Diagnosis of pIMHA was based on the presence of haemolytic anaemia with a packed cell volume of <0.35 L/L, a positive Coombs' test and/or erythrocyte agglutination, spherocytosis and exclusion of an underlying disease. Included were dogs which could be monitored for more than 90 days after initial presentation. Results: Sixty‐one dogs with pIMHA were included. The initial packed cell volume ranged from 0.08 to 0.30 L/L (median 0.16). Immunosuppressive treatment included prednisolone in all the cases; 32 dogs successively received cyclosporine (28), cyclophosphamide (5), leflunomide (2) or human intravenous immunoglobulins (2) in addition. In 33/61 dogs, the drugs were discontinued 67–3372 days (median 334) after beginning of therapy; in 28 dogs, the drug dosage was reduced, but not discontinued until the end of the study. Three dogs developed immune‐mediated thrombocytopenia (days 132, 156 and 680). The observation period ranged from 96 to 4147 days (median 628). A total of 22.9% (14/61) of the dogs developed a relapse after 94–3972 days (median 517). Five dogs were euthanased due to a relapse after 96–1188 days (median 628). Clinical significance: Long‐term prognosis in dogs with pIMHA is favourable. However, a relapse can occur after many years. Relapse was the most common cause of death in dogs with pIMHA that survive more than 90 days.